RT-PCR Protocols - King, Nicola.; King, Nicola.; O’Connell, Joe.; O’Connell, Joe. (Methods in Molecular Biology, 2002)
RT-PCR, the most widely used technique in biomedical research for analyzing gene expression, has proven a significant boon to the molecular investigation of disease pathogenesis. In RT-PCR Protocols, Joe O'Connell has assembled a panel of highly regarded molecular biologists and clinical researchers to describe in detail their most novel, useful, and interesting RT-PCR applications. Here the newcomer will find readily reproducible protocols for highly sensitive detection and quantification of gene expression, the in situ localization of gene expression in tissue, and the cloning of genes, as well as for analyzing T-cell clones and the differential expression of genes. For the expert seeking to extend the usefulness of RT-PCR, there are user-friendly applications that complement the latest technological advances, including laser-capture microdissection (LCM), real-time and quantitative PCR, microarray technology, cDNA cloning, and antibody engineering. Each protocol emphasizes the technical steps critical for experimental success and includes tips on avoiding potential pitfalls, notes explaining the method's scientific basis and its possible sources of error, and comments on how it might best be accommodated to various experimental circumstances. Diverse and wide-ranging, RT-PCR Protocols offers investigators powerful techniques to be used in the molecular investigation of disease pathogenesis and shows how RT-PCR can complement other technological advances in the design of today's new therapeutic strategies.